A case of disseminated intravascular coagulation secondary to Acinetobacter lwoffii and Acinetobacter baumannii bacteremia. Issue 3 (2015) - Baldeo, Candice; Isache, Carmen; Baldeo, Cherisse; Bajwa, Abubakr
Abstract Bacteremia is currently one of the infections with the highest mortality in hospitals [1]. Acinetobacter lwoffii and Acinetobacter baumannii are gram-negative bacteria and both represent opportunistic pathogens. In certain cases, the management can be challenging since these organisms can be highly resistant to antimicrobial agents. Clinical illnesses associated with Acinetobacter include pneumonia, meningitis, peritonitis, endocarditis and infections of the urinary tract and skin [1]. Acinetobacter bacteremia represents a serious and ever increasing problem because of the high associated morbidity and mortality.